Menstrual cycle phase modulates responses to smoking cues in the putamen: Preliminary evidence for a novel target. (1st May 2019) - Franklin, Teresa R.; Jagannathan, Kanchana; Ketcherside, Ariel; Spilka, Nathaniel; Wetherill, Reagan R.
Highlights: The putamen may play a key role in drug cue reactivity in women. In women, dorsal striatal activity may be modulated by the hormonal milieu. Rigorous study of the role of hormones and the dorsal striatum is imperative. Abstract: Background: The preclinical literature identifies the ventral striatum (VS) as a key player in drug-conditioned responses, guiding hypotheses examining neural substrates involved in human drug cue reactivity, including the study of sex differences. Men show a replicable response that includes the VS, while women's responses have been weaker and variable. New evidence suggests that the hormonal milieu modulates women's responses to drug cues in the dorsal striatum (DS), specifically, in the putamen. Here we tested the hypothesis that the hormonal milieu affects neural responses to smoking cues (SCs) in the putamen in women cigarette smokers. Methods: We re-examined our three previous neuroimaging studies of the influence of sex and menstrual cycle (MC) phase effects on SC neuroactivity, incorporating the DS as a region of interest. Results: As previously shown, men exhibited increased ventral medial prefrontal cortex (vmPFC) and VS/V pallidum responses, and women showed increased vmPFC responses that were greater in women during the follicular phase (high estradiol), compared to the luteal phase (high progesterone). Reducing the statistical threshold within luteal phase women revealed select deactivation of the putamen. Conclusions: These preliminary findings shed light upon factors that may modulate drug cue reactivity in women, specifically the influence of hormones on DS responses. Emerging literature suggests that manipulating the hormonal milieu may open a fundamental window into sex-specific treatment targets. More rigorous study of the brain substrates involved in drug cue reactivity and other reward-related behavior that may be influenced by sex and the hormonal milieu is imperative.